Design Automatic Air Conditioning System Control with Passive Infrared Receiver/motion sensor - Diriyanti Novalina, Susi; Sukarwoto, Sukarwoto; Wardani, Ivana; Nathanael Sitompul, Elfrans (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Dr. Ferdinand Lumbantobing Airport faces serious challenges related to the waste of electrical energy in its operations. The quarterly report shows an inconsistent increase in electricity usage, which is largely due to human factors and some technical aspects. The biggest problem is the use of air conditioning and lights that do not need to be constantly active. This article takes a close look at the airport's efforts to address this waste of energy, focusing on the use of air conditioning and constantly burning lights in unused rooms. Measures such as monitoring, automation, sensors, employee extension, and smart appliance development are proposed to address these issues and achieve significant energy savings. This solution will help reduce airport operational costs, increase efficiency, and support environmental conservation.